Pengaruh Pendapatan, Persepsi Keuangan, dan Financial Anxiety terhadap Pengelolaan Keuangan Pribadi Mahasiswa Universitas Persatuan Guru Republik Indonesia Semarang Angkatan 2021 - Mira Dwi Utami; Ika Indriasari; Prianka Ratri Nastiti (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the effect of income, financial perception, and financial anxiety on students' personal financial management. The approach used is quantitative with primary data sources collected through online questionnaires. The population used in the study were students of Universitas PGRI Semarang with a sample size of 333 respondents. The data analysis technique used was multiple linear regression with the help of SPSS Software Version 22. The results of this study indicate that the variables of income, financial perception, and financial anxiety have a positive effect on students' personal financial management.